Sensors for Everyday Life Healthcare Settings - Postolache, Octavian Adrian; Mukhopadhyay, Subhas Chandra; Jayasundera, Krishanthi P.; Swain, Akshya K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Sensors were developed to detect and quantify structures and functions of human body as well as to gather information from the environment in order to optimize the efficiency, cost-effectiveness and quality of healthcare services as well as to improve health and quality of life. This book offers an up-to-date overview of the concepts, modeling, technical and technological details and practical applications of different types of sensors. It also discusses the trends for the next generation of sensors and systems for healthcare settings. It is aimed at researchers and graduate students in the field of healthcare technologies, as well as academics and industry professionals involved in developing sensing systems for human body structures and functions, and for monitoring activities and health.
FPGA Based Smart System for Non Invasive Blood Glucose Sensing Using Photoplethysmography and Online Correction of Motion Artifact -- Sensing System for Bone Health Monitoring -- Cavitas Sensors (Soft Contact Lens Type Biosensor, Mouth-Guard Type Sensor, etc.) for Daily Medicine -- Development of Novel Image Sensor for Root Canal Observation -- Frame-by-Frame Speech Signal Processing and Recognition for FPGA Devices -- Elderly Infrared Body Temperature Telemonitoring System with XBee Wireless Protocol.
Keywords: Electronics; Biotechnology; Medical physics; Biomedical engineering; Electronics and Microelectronics, Instrumentation; Biotechnology; Chemical Bioengineering; Medical Physics; Biomedical Engineering and Bioengineering